'Because of Your Beard I Can Talk to You': Rabbi Froman as Crisis Mediator between Israelis and Palestinians - Rubinstein-Shemer, Nesya (Religions, 2023)
The subject of this essay is the role Rabbi Menachem Froman played as a mediator in crises between Israelis and Palestinians against the background of his interreligious vision of peace and attempts to implement it. Rabbi Froman was very active in this matter and initiated various schemes to promote reconciliation between the Israelis and Palestinians, both in his discussions with religious leaders of the two peoples as well as with politicians in Israel and around the world. The network of contacts and the open discourse that the rabbi developed in order to promote his vision enabled him to serve as a mediator during numerous crises that arose in the Middle East, in general, and Israel in particular. This essay sheds light on Rabbi Froman’s attempts at mediation throughout the years, including the outline of a solution to the Israeli–Palestinian conflict he crafted with the other side. This essay is primarily based on archival materials and newspaper articles about the rabbi that were revealed after his death in 2013. The essay also chronologizes Rabbi Froman’s attempts to serve as mediator for the Israeli and Palestinian leadership and the “jihad for peace” he advocated.